Cooking up recipes for ancient starch: assessing current methodologies and looking to the future. (April 2015) - Barton, Huw; Torrence, Robin
Abstract: Since the publication of Ancient Starch Research (Torrence and Barton, 2006), the number and diversity of archaeological studies utilising analyses of ancient starch have increased to such an extent that we feel it is useful to see how this field is progressing, particularly in the areas of taphonomy and contamination. Starch retrieved from novel contexts, such as dental calculus or adhering to shell tools and ethnographic artifacts, has significantly expanded knowledge about diets, plant use and technology. A key research development has been the addition of studies focused on cereals and maize rather than on underground storage organs as interest in the technique has broadened beyond the tropics. While there are grounds for optimism about the successful incorporation of starch into studies that previously focused on botanical remains with a longer history of research, such as pollen or phytoliths, overcoming significant obstacles is critical to the future of ancient starch research. Experimental archaeology is providing much needed data about the contexts of starch loss, transformation and preservation in the archaeological record, but a general model of the processes involved is still lacking. Recent studies have further confirmed that appropriate physical and chemical conditions permit the preservation of native and unmodified starch over very long time periods. Highlights: Ancient starch research has expanded greatly in the past 10 years. Dental calculus, shell tools and ethnographic items identified as new sources. Analysis of flours is a significant new growth area. Residue analysis benefits from studies of use-wear. Understanding the preservation of ancient starch is essential for future research.